APLIKASI MOBILE ASSISTANT JURUSAN TEKNIK INFORMATIKA UNIVERSITAS PALANGKA RAYA - Nova Noor Kamala Sari; Viktor Handrianus Pranatawijaya; Novera Kristianti; Ressa Priskila; Septian Geges (Jurnal Teknologi Informasi: Jurnal Keilmuan dan Aplikasi Bidang Teknik Informatika, 2022)
The process of attendance information that already exists at Palangka Raya University Informatics Engineering cannot be monitored or is still sharing manually using social media, especially such as informing the presence / presence of lecturers on campus for consultation or signature documents. The purpose of this research is to design and build a Mobile Assistant Application for Informatics Engineering at Palangka Raya University, whose development is based on Location Based Service using a prototype methodology with stages of Communication, Quick plan, Modeling Quick Design, Prototype Formation, Deployment Delivery & Feedback. The modeling of the system uses Java Android object-oriented programming and structured for web applications using the programming language using PHP database using MySQL. From the research conducted, the writer implements the results of the research into the Mobile Assistant Application of the Informatics Engineering Department of Palangka Raya University where there are features of lecturer attendance, class schedules and practicum, as well as assignments. The application of Location Based Service in this application is applied to the Google Map API with geofencing, the central point of the Informatics Engineering department is made a marker that generates a radius where if the application user enters into each radius it will produce a room information notification and send an update of the data to the database as the presence status lecturer.